Projek ikan air tawar :Aqua Blue Village Company / Rohaida Arifin ...[et al.] - Arifin, Rohaida; Ramli, Nursabila; Ahmad Azmi, Nur Diana; Nural Anuar, Nur Hazyyah; Saidina Ali, Saidatul Noor Akmal (2008)
We share the same vision, mission and objectives in order to commercialize these types of fishes to the outside of country. In order to commercialize this field to over the country, we have to alert the society about this type of fish that highly demand nowadays. Keli, Patin and Talapia are just three type of fish that the fish maniac’ got crazy for. We have to make an approach to the society in order to them to real live that there are many other types of fishes which are greater that the sea fish which can be commercialize